2019
DOI: 10.1177/2381468319856306
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis and Comparison of Point of Care Testing and Central Laboratory Testing

Abstract: Background. In response to demand for fast and efficient clinical testing, the use of point-of-care testing (POCT) has become increasingly common in the United States. However, studies of POCT implementation have found that adopting POCT may not always be advantageous relative to centralized laboratory testing. Methods. We construct a simulation model of patient flow in an outpatient care setting to evaluate tradeoffs involved in POCT implementation across multiple dimensions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…One of the key advantages of using point of care systems is the increased patient flow (Harder et al 2019). If the healthcare processes are not redesigned to take advantage of reduced turnaround time, the benefits portrayed by the point of care system can be distorted.…”
Section: Modeling Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key advantages of using point of care systems is the increased patient flow (Harder et al 2019). If the healthcare processes are not redesigned to take advantage of reduced turnaround time, the benefits portrayed by the point of care system can be distorted.…”
Section: Modeling Results and Discussionmentioning
confidence: 99%
“…Reduced turnaround time between patient sample collection and test results is the primary benefit because test results are available to healthcare decision-makers within minutes. Nevertheless, the ability of clinical processes (patient process) to take advantage of the reduced turnaround time is the critical determinant of the effects of point-of-care testing on patient care (Harder et al 2019, Lingervelder et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…However, core laboratory assays typically produce more analytically robust values, have a wider dynamic range, and have a higher overall throughput. 10 As the literature on GFAP and UCH-L1 matures, it would be helpful to have a clear understanding on how values of these biomarkers differ when measured using different platforms. Conversion of ARCHITECT to i-STAT values will enable direct comparison of assay results derived from the two platforms.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, it was concluded that the use of POCT in hospital EDs significantly contributes to cost management compared to using conventional diagnostic methods, further emphasizing their importance in cost-effectiveness [ 66 ]. However, it is worth noting that the cost of POCT can fluctuate, sometimes exceeding that of traditional methods, depending on the clinical setting, target condition, and test quality [ 67 ].…”
Section: Cost-effectiveness Of Lfamentioning
confidence: 99%